The Need for a Double Kinship: Children's Literature, Intergenerational Relationships, and Climate Change - Joosen, Vanessa (Cahier voor Literatuurwetenschap, 2024)
This article offers a plea for a consciously hopeful discourse in children’s literature that addresses the environmental crisis—a discourse that puts intergenerational dialogue and kinship more central than it currently does. To do so, the article first explores the two meanings of the word “kinship” as they have been developed by Marah Gubar in children’s literature studies and by Donna Haraway in posthumanism. It then offers an analysis of four children’s books: one that relies on posthuman kinship but leaves out intergenerational kinship (The Fate of Fausto by Oliver Jeffers), one that features intergenerational but limited posthuman kinship to address the environmental crisis (David Almond and Levi Pinfold’s The Dam), one that thematizes the failure of both (a short story from Shaun Tan’s Tales From the Inner City) and one that features both to produce hope (Bone Music by David Almond). Bone Music shows that posthumanist and intergenerational kinship can reinforce each other so that people feel reinvigorated in their hope, willingness and agency to confront the systems that need to change.